2010
DOI: 10.1042/bst0380955
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing of tau

Abstract: Tau aggregation is a hallmark of several neurodegenerative diseases, including AD (Alzheimer's disease), although the mechanism underlying tau aggregation remains unclear. Recent studies show that the proteolysis of tau plays an important role in both tau aggregation and neurodegeneration. On one hand, truncation of tau may generate amyloidogenic tau fragments that initiate the aggregation of tau, which in turn can cause toxicity. On the other hand, truncation of tau may result in tau fragments which induce ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 81 publications
(103 reference statements)
2
101
0
1
Order By: Relevance
“…40 The lack of colocalization between TaunY197 or Tau-Y197 with the MN423 antibody might be due to a proteolytic cleavage that ablates position 197, perhaps generated by a chymotrypsin-like endopeptidase. 42,43 Collectively, these data indicate that nitration at Y197 occurs before the appearance of detectable tau pathology and colocalizes with only a subset of tau pathology during the initial stages of tangle formation in AD.…”
Section: Timing Of Nitration During Tangle Evolution In Ad Pathogenesismentioning
confidence: 94%
“…40 The lack of colocalization between TaunY197 or Tau-Y197 with the MN423 antibody might be due to a proteolytic cleavage that ablates position 197, perhaps generated by a chymotrypsin-like endopeptidase. 42,43 Collectively, these data indicate that nitration at Y197 occurs before the appearance of detectable tau pathology and colocalizes with only a subset of tau pathology during the initial stages of tangle formation in AD.…”
Section: Timing Of Nitration During Tangle Evolution In Ad Pathogenesismentioning
confidence: 94%
“…Indeed, seeding of protein aggregation in vitro appears to work universally, and fits with the structural model of aggregation as the addition of new strands to a growing amyloid fibril (8). This imparts sequence specificity to the seeding process as the incorporation of non-homologous sequences into the highly ordered in-register stacking of identical side chains in the fibril core is likely to be energetically disfavoured (13,20,21). The seeding concept appears to hold true both in cell culture and in vivo, even for non-prion aggregation-associated peptides and proteins, which have hence been called prionoids (22).…”
Section: Introductionmentioning
confidence: 94%
“…Here we investigate whether an endogenously expressed protein that possesses amyloidogenic potential but aggregates neither under normal nor pathological conditions, can be induced to do so by seeding with a peptide consisting of an amyloidogenic fragment of its own sequence. The use of amyloidogenic fragment peptides is motivated by the observation that aggregation of disease-associated amyloidogenic proteins can be seeded by such peptides in vitro (10,11) and that truncations of amyloid proteins have been associated with increased seeding potential in vivo (12,13). Moreover it has been shown that amyloidogenic peptides and proteins are generally much more efficient at seeding aggregation of homotypic sequences (14)(15)(16)) although examples of cross seeding do exist (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a large number of studies show that prionoids associated with CNS proteinopathies, when applied exogenously to glial cells, activate innate immunity through pattern recognition receptors and induce a proinflammatory response (50,53). Furthermore, there is some evidence that the resulting response to the DAMPs could modify the protein aggregate via various posttranslational modifications, such nitration, oxidation, or proteolysis, enhancing toxicity or promoting additional aggregation (54)(55)(56). Though studies of Aβ aggregates acting as DAMPs have until recently dominated this area of investigation, the finding that intracellular protein aggregates can be secreted provides a mechanism whereby even tau, α-synuclein, and other intracellular aggregates could activate the innate immune system upon secretion (57)(58)(59).…”
Section: Figurementioning
confidence: 99%